Copper solid amalgam electrode as a simple and sensitive tool for voltammetric determination of the antineoplastic drug 5-fluorouracil in pharmaceuticals - Šelešovská, Renáta; Janíková, Lenka; Štěpánková, Michaela; Chýlková, Jaromíra (My University, 2017)
Voltammetric behavior of the antineoplastic drug 5-ﬂuorouracil is for the ﬁrst time studied on polished copper solid amalgam electrode. It was proved that the presence of the copper in the electrode material is advantageous for the determination of 5-ﬂuorouracil, and one well-developed cathodic signal belonging to the reduction of the absorbed complex of 5-ﬂuorouracil–Cu(II) was found as suitable for its precise determination. The highest response was recorded in Britton–Robinson buffer of pH 8 and excellent results like repeatability of measurements and determination as well or limit of detection (1.2 9 10-9 mol L-1) were reached. Moreover, the proposed method was successfully applied to the analysis of pharmaceutical sample with excellent recovery (97.0–100.9%).
Měděná pevná amalgámová elektroda jako jednoduchý a citlivý nástroj pro stanovení léčiva 5-fluorouracilu ve farmaceutických přípravcích.
Keywords: 5-Fluorouracil; Copper solid amalgam electrode; Voltammetry; Determination; Pharmaceutical samples; 5-fluorouracil; měděná pevná amalgámová elektroda; voltametrie; stanovení; farmaceutické přípravky